Analysis of Odd Semester Exam Questions for Indonesian Class VII SMP Negeri 35 Pekanbaru Academic Year 2019-2020 - Wulandari; Nazirun (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Analysis of items for the odd semester exam for Indonesian class VII SMP Negeri 35 Pekanbaru for the 2019-2020 academic year. In answering exam questions, there are still many students who are remedial or incomplete in doing the questions. Of course, many students who cannot answer the questions are mentioned by the lack of students in learning, but the questions made by the Subject Teacher Consultative Team (MGMP) are still available. which students do not understand. Good questions must have a scope, not too easy and not too difficult, if the questions given are too difficult, the students are declared incomplete in doing the questions. The reason the author is researching about the Odd Semester Exam Items for Indonesian Language Subjects Class VII SMP Negeri 35 Pekanbaru for the 2019-2020 Academic Year is to describe, analyze and interpret the level of difficulty of the odd semester exam questions for Indonesian language subjects for class VII SMP Negeri 35 Pekanbaru year lessons 2019/2020. The problem in this research is how to analyze the Difficulty Index, Distinguishing Power Index and the function of distractors (detractors) of Odd Semester Exam Questions for Indonesian Language Subject Class VII SMP Negeri 35 Pekanbaru in the 2019/2020 academic year. As is known, item analysis or item analysis is an assessment of test questions in order to obtain a set of questions that have a set of questions so that information is obtained about the ugliness of a question and instructions for making improvements. This study aims to describe, analyze and interpret the level of difficulty of the odd semester exam items for Indonesian class VII SMP Negeri 35 Pekanbaru in the 2019/2020 school year. The population of this research is the seventh grade students of SMP Negen 35 Pekanbaru in the 2019/2020 school year, totaling 50 people. Quantitative research method using interview and documentation techniques. The results showed that the index of difficulty level of the odd semester exam items on average was in the easy category while the 91% difference power index of the odd semester exam items was categorized as feasible, thus the hypothesis was accepted.